The Islamic Law of War - Al-Dawoody, A. author. aut Link
XIII, 338 p.
Keywords: Al-Dawoody examines the justifications and regulations for going to war in both international and domestic armed conflicts under Islamic law. He studies the various kinds of use of force by both state and non-state actors in order to determine the nature of the Islamic law of war.